The influence of the leg cutting on the core losses in the amorphous modular transformers. Issue 3 (5th May 2015) - Demenko, Ivo Doležel, Kay Hameyer, Wojciech Pietrowski; Krzysztof Zawirski, Andrzej; Tomczuk, Bronislaw; Koteras, Dariusz; Waindok, Andrzej
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – In a modular transformer with a wounded amorphous core, the authors should make some cutting to limit the eddy currents in its magnetic ribbon. The purpose of this paper is to deal with 3D magnetic field analysis, including the eddy currents induced by varying frequency of power. The influence of the core leg cutting on the power losses values, in the three variants of a one-phase modular transformer structure, has been presented. Design/methodology/approach – 3D field problems including eddy currents of various frequency were analysed using the electrodynamic potentials and V within the finite element method. The wave method and iterative one of the laminated core homogenization, have been employed. The values of the calculated losses have been verified experimentally. Findings – The reduction of the core losses by axial cutting of the transformer legs is an efficient approach for the loss limitation. The wave method is not acceptable for homogenization of the amorphous core for its operation above 1 kHz. The iterative method is the better way to perform the homogenization. Research limitations/implications – Due to very thin (less than 50 μm) amorphous ribbon, the unhomogenization of the laminated magnetic core should be performed. Thus, the solid core with equivalent parameters has been assumed for the computer simulations. For the frequencies above 1 kHz, the iterative method should be used to determine the equivalent electrical conductivity of the solid substitute core. Originality/value – Using the wave method with the electrodynamic similarity laws and assuming the wave penetration depth, the equivalent electrical conductivity of the homogenized core, has been determined. This approach is valid for supply frequencies below 1 kHz. For the higher frequencies the authors had to use the iterative method. It seems to be valid for another cores with amorphous and nanocrystalic ribbons. For the modular amorphous core it is only way to calculate the losses in the solid geometry of the homogenized laminated magnetic circuit.